2014
DOI: 10.1007/s00775-014-1127-4
|View full text |Cite
|
Sign up to set email alerts
|

Cognate and noncognate metal ion coordination in metal-specific metallothioneins: the Helix pomatia system as a model

Abstract: The Helix pomatia metallothionein (MT) system, namely, its two highly specific forms, HpCdMT and HpCuMT, has offered once again an optimum model to study metal-protein specificity. The present work investigates the most unexplored aspect of the coordination behavior of MT polypeptides with respect to either cognate or noncognate metal ions, as opposed to the standard studies of cognate metal ion coordination. To this end, we analyzed the in vivo synthesis of the corresponding complexes with their noncognate me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 34 publications
3
47
2
Order By: Relevance
“…CaCdMT and CaCuMT synthesis under Zn-supplementation yielded the expected results, fully comparable to those previously reported for the H. pomatia orthologous isoforms. Hence, CaCdMT afforded unique, well-folded Zn 6 -CaCdMT complexes, with features totally alike to those of Zn 6 -HpCdMT [11,15], while CaCuMT exhibited its unsuitability for Zn 2+ coordination by yielding two complexes, Zn 5 -and Zn 6 -CaCuMT, with rather poor folding. Interestingly, the CaCd/CuMT isoform showed even worse Zn-binding aptitudes, since three species of significant abundance were recovered here (Zn 4 -, Zn 5 -and Zn 6 -CaCd/CuMT) showing a CD spectrum revealing a complete lack of chirality.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…CaCdMT and CaCuMT synthesis under Zn-supplementation yielded the expected results, fully comparable to those previously reported for the H. pomatia orthologous isoforms. Hence, CaCdMT afforded unique, well-folded Zn 6 -CaCdMT complexes, with features totally alike to those of Zn 6 -HpCdMT [11,15], while CaCuMT exhibited its unsuitability for Zn 2+ coordination by yielding two complexes, Zn 5 -and Zn 6 -CaCuMT, with rather poor folding. Interestingly, the CaCd/CuMT isoform showed even worse Zn-binding aptitudes, since three species of significant abundance were recovered here (Zn 4 -, Zn 5 -and Zn 6 -CaCd/CuMT) showing a CD spectrum revealing a complete lack of chirality.…”
Section: Discussionmentioning
confidence: 94%
“…The third isoform was natively isolated as a mixed Cd and Cu complex, and for this reason named CaCd/CuMT, but the poor level of expression and the lack of metal response of its encoding gene suggested a residual role, if any, in the snail metabolism of metals, either physiological or xenobiotic. The examination of the similarities and differences between the three CaMT protein sequences promptly revealed that the comparative analysis of their metal binding abilities -and also in relation to those of the H. pomatia MTs (HpCdMT and HpCuMT, already extensively analyzed [11,15]) -could yield invaluable information about the determinants of metal specificity in metallothioneins. As a rule-of-thumb, we have unequivocally shown that recombinant synthesis of an MT peptide as a complex with its cognate metal produces unique, energetically optimized complexes, while when an MT is forced to coordinate noncognate metals, it yields a mixture of complexes of different stoichiometry and/or folding, none of which achieves a definite energy well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In HpCd 6 MT, Cd(II) ions are bound in tetrahedral coordination each by four thiolate ligands in the form oligonuclear metal thiolate clusters, for which the structure remains to be determined. In Cu 12 ‐HpCuMT, spectroscopic analysis indicate that Cu(I) is organized in the form of oligonuclear Cu(I) thiolate clusters with features very similar to mammalian Cu 12 ‐MT in which metals are bound predominantly in trigonal coordination . Stability of the expressed Cd 6 ‐HpCdMT and Cu 12 ‐HpCuMT complexes was demonstrated by their metal exchange inertness.…”
Section: Copper Mts In Molluscsmentioning
confidence: 99%